The Impact of Problem-based Learning Models on Social Studies Learning Outcomes and Critical Thinking Skills for Fifth Grade Elementary School Students - I Made Aditya Dharma; Nyoman Ayu Putri Lestari (Jurnal Ilmiah Sekolah Dasar, 2022)
Critical thinking skills are needed in social studies learning, but the fact is that students' critical thinking skills in elementary schools are not optimal, so that it has an impact on student learning outcomes under the KKM. This study aims to analyze the effect of the problem-based learning model on learning outcomes and students' critical thinking skills. This type of research is quantitative research with a quasi-experimental and the design used is posttest only control group design. The population in this study were fifth grade elementary school students. Random sampling was used to determine the sample, while the total sample size was 68 students from two different schools. To test the hypothesis, one-way ANOVA and Manova analysis were used. The test results show that there is an effect of problem-based learning on social studies learning outcomes and students' critical thinking skills. So, it can be concluded that the problem-based learning has a significant effect on improving social studies learning outcomes and students' critical thinking skills compared to using conventional learning models. The implication of this research is that teachers are expected to be able to implement this problem-based learning model in the learning process, so that it can improve students' ability to understand subject matter easily and quickly during the learning process.